Are You Bioconservative, Transhumanist, or Something in Between? Take the Test and Find Out - Selak, Marija (2011)
One of the most present bioethical debates in media is the one concerned with the use of technology in enhancing human creative and biological possibilities. Transhumanist movement, which is supporting the idea of human enhancement, has expanded from science fiction to mainstream thinking and even has become a subject of scientific evaluation (Bostrom). Ethical positions concerning human enhancement technologies range from transhumanism to bioconservatism. While on one side transhumanists believe that human enhancement technologies should be made widely available and that individuals should have the right to choose which they want to use, bioconservatives are generally opposed to modifying human nature. This presentation, in questions concerning human dignity and moral judgement, will show both, transhumanism argumentation (Bostrom) on one side and bioconservatism thinking (Fukuyama, Habermas) on the other. Also, to demonstrate actuality of transhumanist-bioconservative debate, the one of the media most accompanied moments of this debate (Sloterdjik - Habermas case) will be discussed and the populist rhetoric of transhumanist supporters (Bostrom) will be shortly reviewed.